MENAKAR PERUBAHAN SOSIO-KULTURAL MASYARAKAT TANI AKIBAT MISKONSEPSI MODERNISASI PEMBANGUNAN PERTANIAN - Kadhung Prayoga; Suryani Nurfadillah; Manna Saragih; Adietya Muhammad Riezky (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
The green revolution is an evidence of how agricultural modernization was interpreted by the Indonesian government. An agricultural acceleration program that aimed to improve the effectiveness of farmers' work. Its success has made Indonesia a self-sufficient country for rice, however, this modernization of agriculture has left many sins that have caused changes in the lives of farmers, both socially and economically. The modernization of agriculture actually led to a step backward in agricultural development because of the government's mistake in interpreting modernization itself. The purpose of this paper was to explain in detail what socioeconomic changes that actually occur because of errors in interpreting modernization. The approach used in this study is a qualitative approach using descriptive methods. This study used literature study method to obtain secondary data and the interpretation reference to various literature was used to analyse the data. The analysis led to result that there have been many socio-cultural and economic changes in the structure of life of the village community. Many women lose their job as a farmer and they were marginalized, there was no division of labor based on gender, rapid and unplanned urban growth, stagnant regeneration, overdependence on industry,germplasm destruction, mutual cooperation culture degradation, caste system emergence in farming communities, the weakening of local institutional functions, farmer was only as an extension object, and others. In the future, agricultural modernization must be based on the peasant community and put the whole rural development perspective based on the empowerment approach.